Monitoring and Evaluation of the Educational Unit Curriculum at the Takhfidz Al Husna International Islamic Boarding School - Arif Wibowo (Universitas Muhammadiyah Enrekang, 2025)
To maintain the alignment of material and developmental demands that are always growing rapidly, a curriculum must always be evaluated regularly. This study reviews the monitoring and evaluation of the education unit curriculum at the Takhfidz Al Husna International Boarding School in Mayong Jepara. Which aims to find out how the curriculum at Takhfidz Al Husna International Boarding School Mayong Jepara and find out why the importance of monitoring and evaluating the curriculum at Takhfidz Al Husna International Boarding School Mayong Jepara and also what the implications of monitoring and evaluating the curriculum at Takhfidz Al Husna International Boarding School Mayong Jepara. This research uses the System Literature Review (SLR) method. This SLR method is used to identify, review, evaluate, and interpret all available research with the topic area of interesting phenomena, with certain relevant research questions. From the results of the research, it was found that the development of the education unit curriculum was integrated with the boarding school curriculum. Judging from the administration, here it is very complete all kinds of curriculum content itself. Implementation is also very efficient, because the subject matter is directly practiced on a daily basis. Continuity is also very good, because all student activities from waking up to going to bed can be set without pausing other activities that interfere. The vision, mission and objectives of the character development of the education unit curriculum have also produced students who excel at the provincial and even national levels. However, the results of researcher observations still have several things that need to be maximized, namely special classrooms for formal education, so that students are more focused and the implementation of bilingual programs that have not been maximized.